Short and medium- to long-term impacts of nature-based solutions on urban heat. (June 2020) - Augusto, Bruno; Roebeling, Peter; Rafael, Sandra; Ferreira, Joana; Ascenso, Ana; Bodilis, Carole
Highlights: Nature based solutions were used to reduce urban heating and mitigate urban sprawl. The effects were measured in the urban heat fluxes. WRF-SUEWS and SULD constitute a useful tool for policy decision. Urban compacting reduces the effect of nature based solutions on urban heat. Abstract: Many cities are growing and becoming more densely populated, resulting in land use changes, which promotes an increase in urban heating. Nature-based solutions (NBS) are considered sustainable, cost-effective and multi-purpose solutions for these problems. While various studies assess the effects of NBS on urban heat or urban sprawl/compaction, no studies assess their cumulative effect. The main objective of this study is to assess the short-term and medium- to long-term impacts of NBS on urban heat fluxes, taking as a case study the city of Eindhoven in The Netherlands. An integrated modelling approach, composed of a coupled meteorological and urban energy balance model (WRF-SUEWS) and an hedonic pricing simulation model (SULD), is used to assess urban heat fluxes and urban compaction effects, respectively. Results show that, in the short-term, NBS have a local cooling effect due to an increase in green/blue spaces and, in the medium to long-term, an urban compaction effect due to attraction of residents from peripheral areas to areas surrounding attractive NBS. This study provides evidence that NBS can be used to reduce the effects of urban heating and urban sprawl and that an integrated modelling approach allows to better understand its overalleffects.